Germline and Somatic BRCA1/2 Mutations in 172 Chinese Women With Epithelial Ovarian Cancer - You, Yan; Li, Lei; Lu, Junliang; Wu, Huanwen; Wang, Jing; Gao, Jie; Wu, Ming; Liang, Zhiyong (Frontiers in Oncology, 2020)
Objective Despite several nationwide cohort studies on germline BRCA1/2 mutations and several small cohort studies on somatic BRCA1/2 mutations in Chinese epithelial ovarian cancer (EOC) patients, little is known about the impact of these findings on survival outcomes in this population. In this study of 172 retrospectively recruited Chinese EOC patients, germline and somatic BRCA1/2 mutations and their value for predicting survival outcomes were evaluated. Methods Unselected patients who visited the study center from January 1, 2011, to January 1, 2015, were recruited and asked to provide peripheral blood samples for this study if they were pathologically confirmed to have primary EOC. All patients received staging surgeries or debulking surgeries systemic platinum-based chemotherapy, and the patients were then followed up to December 1, 2017. DNA was extracted from formalin-fixed, paraffin-embedded (FFPE) sections and peripheral blood and sequenced for somatic and germline testing, respectively. The demographic and clinicopathological characteristics of the patients were collected to analyze the distribution of BRCA mutations in subgroups. Survival outcomes were compared among various BRCA mutation statuses using univariate and multivariate models. Results In 59 (34.1%) patients, 64 variants were identified, including variants of unknown signiﬁcance (VUS) in 19 patients (11.0%) and pathogenic or likely pathogenic variants in a partially overlapping set of 41 patients (23.8%). Germline BRCA mutations, somatic BRCA mutations, BRCA1 mutations in general, and BRCA2 mutations in general were found in 35 (20.3%), 7 (4.1%), 28 (16.3%) and 13 (7.6%) patients, respectively. Five recurrent mutations were identified. Personal and family cancer history as well as hereditary breast and ovarian cancer (HBOC) criteria were associated with deleterious BRCA mutations both overall and in the germline specifically, whereas only age at diagnosis of EOC was associated with somatic BRCA mutations. In univariate and Cox regression analyses, patients with BRCA1/2 mutations in general had significant improvements in progression-free survival (PFS) and overall survival (OS). Conclusions In Chinese EOC patients, the distributions and risk factors associated with germline and somatic BRCA1/2 were similar to those previously reported in international studies. Deleterious BRCA mutations in general were associated with improved survival outcomes in this cohort.